Abnormal strong burn-in degradation of highly efficient polymer solar cells caused by spinodal donor-acceptor demixing - Ning Li (Nature Portfolio, 2017)
Liet al. study degradation in organic photovoltaics from a morphological perspective. They find that donor and acceptor phases undergo excessive demixing via spinodal decomposition resulting in a reduction of charge generation. Demixing is due to the inherently low miscibility of both materials.